2008
DOI: 10.1097/pcc.0b013e31818c82b4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled blinded study of three bronchodilators in infants with respiratory syncytial virus bronchiolitis on mechanical ventilation*

Abstract: Similar statistically significant bronchodilation occurred after all three bronchodilators as indicated by a decrease in peak inspiratory pressure and respiratory system resistance, but these changes were small and probably clinically insignificant. However, side effects of bronchodilators, such as tachycardia, also occurred, and these may be clinically significant. Thus the benefit of bronchodilator treatment in these patients is small, does not differ among the drugs we studied and of questionable value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…56,61 One study in a critical care setting showed a small decrease in inspiratory resistance after albuterol in one group and levalbuterol in another group, but therapy was accompanied by clinically significant tachycardia. 62 This small clinical change occurring with significant adverse effects does not justify recommending albuterol for routine care.…”
Section: Action Statement Profile Kasmentioning
confidence: 99%
“…56,61 One study in a critical care setting showed a small decrease in inspiratory resistance after albuterol in one group and levalbuterol in another group, but therapy was accompanied by clinically significant tachycardia. 62 This small clinical change occurring with significant adverse effects does not justify recommending albuterol for routine care.…”
Section: Action Statement Profile Kasmentioning
confidence: 99%
“…Of these, 5 infants were recruited from the MICU, 6 were recruited from the ICP, and 4 from the Inpatient Units. There were 10 males and 5 females with a median age of 2.0 (0.4-18) months, median weight of 5.8 (3)(4)(5)(6)(7)(8)(9)(10)(11) kg and median height of 60 (50-84) cm. Median time to acute stabilization was 4 (1-6) days, time between initial and final CO recording was 2.5 (0.8-7.2) days and length of hospitalization was 3.6 (1.6-8.9) days.…”
Section: Resultsmentioning
confidence: 99%
“…Heart rate (HR) is generally used as a surrogate for CO but can be misleading with infants with RSV bronchiolitis, who tend to be tachycardic due to various factors including medical interventions [11,12]. Clinical exam may be suboptimal [13] to determine CO, as infants with RSV bronchiolitis typically have elevated HR, high respiratory rate (RR), pulmonary adventitious sounds and a normal heart size on radiological exam.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Levin and co-workers confirmed the absence of beneficial effect of bronchodilators (i.e. norepinephrine, levalbuterol, and racemic albuterol) (Levin et al, 2008).…”
Section: Treatment Of Severe Rsv Lrtdmentioning
confidence: 97%